Land Resources : now and for the future - Young, Anthony (Cambridge : Cambridge University Press, 1998)
This book provides an authoritative review of the resources of soils, water, climate, forests and pastures on which agriculture depends. It assesses the interactions between land resources and wider aspects of development, including population and poverty. Unless action is taken, the developing world will face recurrent problems of food security and conflict. The book gives some forcefully-expressed criticisms of current methods of assessing land degradation and placing an economic value on land. It should be read by all involved in rural development, including scientists, economists, geographers, sociologists, planners, and students of development studies. It provides a summary and perspective of the field of land resources, and suggests improvements needed to conserve resources for future generations. The hardback edition of the book received excellent reviews.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Land use, Rural -- Planning; Agricultural conservation; Renewable natural resources; Sustainable development; Land use, Rural -- Developing countries -- Planning; Agricultural conservation -- Developing countries; Renewable natural resources -- Developing countries; Sustainable development -- Developing countries